Evaluasi jenis dan penataan tanaman median jalan Sunset Road, Kuta untuk keselamatan pengendara - Apriani, Adelia; Krisnandika, Anak Agung Keswari; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2022)
This study aims to evaluate the type and arrangement of plants on the median of Sunset Road with a length of 1,561 m which is divided into 7 segments based on road characteristics and driver safety criteria. The survey method with a qualitative descriptive analysis approach and data collection techniques in the form of observation, interviews and literature study were used in this study. The results of the evaluation showed that 12.5% of plant species were categorized as unsuitable and potentially dangerous to motorists, 50% were suitable and 37.5% were very suitable to be planted on the Sunset Road median. Plants in the median of the road should have more than 1 function, based on each function, 93.8% of plants on Sunset Road have a directing function, 62.5% have a function as a vehicle light blocking, 56.5% have a separator function and 18.8% of plants have a safety function. Completeness of plant composition in terms of leaf texture, height and color in each segment ranged from 56-89%. In addition, improper arrangement was also found in several segments, especially segments 2-5. It can be concluded that there is a mismatch of species and plant arrangement in the median of Sunset Road in terms of the driver safety criteria used in this study.